Faktor Yang Mempengaruhi Minat Siswa Untuk Melanjutkan Pendidikan Ke Perguruan Tinggi di SMK 4 Kota Jambi - Lili Andriani (Jurnal Ilmiah Dikdaya, 2021)
This study aims to determine the internal and external factors as well as to dominate the internal and external factors that influence students' interest in continuing their education to tertiary education at SMK Bangun Nusantara Kab. Bungo. This study used a qualitative descriptive research method and the population as well as the sample in this study were 40 students. The research data were obtained through observation, questionnaires, interviews, and documentation. This research shows that the interest of students to continue their education to higher education from internal factors is quite good. Meanwhile, the external factors are not good enough. And the factors that most influence student interest are internal factors consisting of intelligence, attitude and motivation. The results of the study were calculated using the measurement scale based on the Likert scale, namely the score value and using the TCR formula, the results of which were calculated as follows: Factors affecting student interest in continuing their education to tertiary education at SMK Bangun Nusantara Kab. Bungo: Internal factors consist of 23 alternative questions consisting of 74% intelligence, 70% attitude, 70% talent, and 77% motivation. The average result of internal factors is 71.86% which is quite good. Meanwhile, external factors consist of 17 alternative questions consisting of social environment 66%, and non social environment 60%. With an average result of 64.47%. Family, community and non-social environments are very influential on the desire of students to continue their education to higher education. So it can be said that external factors greatly influence students' interest in continuing to higher education.